2017
DOI: 10.1111/cbdd.12992
|View full text |Cite
|
Sign up to set email alerts
|

Novel 19F‐MRS β‐galactosidase reporter molecules incorporated nitrogen mustard analogues

Abstract: In this study, we propose a novel molecular platform-integrated fluorinated antitumor nitrogen mustards for F-MRS assay of β-galactosidase (β-gal) activity. Following this idea, we have designed, synthesized, and characterized 2-fluoro-4-[bis(2'-chloroethyl)amino]phenyl β-D-galactopyranoside 5, 2-fluoro-4-{bis[2'-O-(β-D-galactopyranosyl)ethyl]amino}phenyl β-D-galactopyranoside 8, 2-fluoro-4-{bis[[1″-(β-D-galactopyranosyl)-1″, 2″, 3″-triazol-4″-yl]methyl] amino}phenyl β-D-galactopyranoside 14 and 2-fluoro-4-{bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The structures of AZ-M1/AZ-1 and AZ-M2/AZ-2 were confirmed by NMR and HRMS data. The molecular/quasimolecular ions of AZ-M1 and AZ-1, as well as AZ-M2 and AZ-2, showed the introduction of one and two galactopyranosyl units to AZ-M1/AZ-1 and AZ-M2/AZ-2, respectively, in which the β-D-galactopyranoside configuration was determined by 1H/13C NMR data of the anomeric protons at δ H-1′ δ H-1′′ 4.90-5.30 ppm and their coupling constants J 1′,2′ J 1′′,2′′ 8.0 Hz while maintaining the corresponding anomeric C-1′/C-1′′ at δ C-1′ δ C-1′′ 99.5-104.0 ppm in accordance (Supporting Information, Supplementary Figures S4-S13), which are in agreement with the typical characteristics for the identification of the anomeric β-D-configuration (Yu et al, 2005;Kodibagkar et al, 2006;Liu et al, 2007;Yu et al, 2008a;Yu et al, 2008b;Yu et al, 2012b;Yu et al, 2013;Yu et al, 2017).…”
Section: Alizarin β-D-galactopyranoside Synthesissupporting
confidence: 84%
See 1 more Smart Citation
“…The structures of AZ-M1/AZ-1 and AZ-M2/AZ-2 were confirmed by NMR and HRMS data. The molecular/quasimolecular ions of AZ-M1 and AZ-1, as well as AZ-M2 and AZ-2, showed the introduction of one and two galactopyranosyl units to AZ-M1/AZ-1 and AZ-M2/AZ-2, respectively, in which the β-D-galactopyranoside configuration was determined by 1H/13C NMR data of the anomeric protons at δ H-1′ δ H-1′′ 4.90-5.30 ppm and their coupling constants J 1′,2′ J 1′′,2′′ 8.0 Hz while maintaining the corresponding anomeric C-1′/C-1′′ at δ C-1′ δ C-1′′ 99.5-104.0 ppm in accordance (Supporting Information, Supplementary Figures S4-S13), which are in agreement with the typical characteristics for the identification of the anomeric β-D-configuration (Yu et al, 2005;Kodibagkar et al, 2006;Liu et al, 2007;Yu et al, 2008a;Yu et al, 2008b;Yu et al, 2012b;Yu et al, 2013;Yu et al, 2017).…”
Section: Alizarin β-D-galactopyranoside Synthesissupporting
confidence: 84%
“…We observed that FIGURE 2 | The 1 H-MRI of an Fe 3+ -alizarin complex. MRI acquisition parameters: 1 H-MRI, 200 MHz, matrix size: 128 × 128, FOV: 40 mm × 40 mm, slice thickness: 2 mm; receiver bandwidth: 20 kHz, T 1 -map: saturation recovery spin-echo sequence, TR 200, 400, 600, 800, 1,000, 2000, 3,000, and 6,000 ms, respectively, TE 15 ms; T 2 -map: multi-echo SE sequence, TE 10,20,30,40,50,60,70,80,90,100,110,120,130,140,150,and the phenolic hydroxyl groups at 1,2-positions of alizarin have excellent site-reaction selectivity due to the various electronic deficiency/sterically hindered effects (Mahal et al, 2011) and apparently different pKa values: pKa (2-OH) 5.98 ± 0.05, whereas pKa (1-OH) 9.88 ± 0.05 (Das et al, 1995;Das et al, 2002), which suggested that the phase-transfer catalysis method at pH 8-9 could provide regio-and stereoselective synthesis of AZ-1, as exploited previously for β-gal 19 F-MRS/MRI reporters (Yu et al, 2005;Kodibagkar et al, 2006;Liu et al, 2007;Yu et al, 2008a;Yu et al, 2008b;Yu et al, 2012b;Yu et al, 2013;Yu et al, 2017). To the well-stirred solution of alizarin in CH 2 Cl 2 -H 2 O (pH 8-9) using tetrabutylammonium bromide (TBAB) as a catalyst at 50°C, an equimolar amount of 2, 3, 4, and 6-tetra-O-acetylα-D-galactopyranosyl bromide was dropped under N 2 atmosphere for around 1 h; alizarin 2-O-2′, 3′, 4′, and 6′tetra-O-acetyl-β-D-galactopyranoside AZ-M1 was isolated purely at the yield of 78%.…”
Section: Alizarin β-D-galactopyranoside Synthesismentioning
confidence: 77%